(untitled) (International Journal of Innovative Technologies in Economy, 2022)
This paper reviews the strategic ways of developing the mining industry, as well as reveals the shortcomings of the legal framework hindering the development of the sector, and discusses the accounting complexity. The article substantiates that the mining industry has a significant share in the national economy of the Republic of Armenia, and the goal of the development of the sector is to contribute to the sustainable development of the country by highlighting the existing problems, as well as increase the ranking and competitiveness of the RA mining companies in the international market.